The mobile connection : the cell phone's impact on society - Ling, Richard Seyler (Morgan Kaufmann series in interactive technologies., 2004)
"Based on research conducted in dozens of countries, this book examines the once-unexpected interaction between humans and cell phones, and between humans, period. The discussion and projections about the future of the telephone should give designers everywhere a more informed practice and process, and provide researchers with new ideas to last years."--Jacket